Innovation of Singing Methods in Overcaming Phonetic Difficulties of Arabic Student at Nurul Chotib Islamic Boarding School - al hidayah, Hanik; Asy’ari, Hasyim; Zainal, Muhammad Rizki (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2025)
Phonetic difficulties remain a significant barrier for non-native Arabic learners, especially in mastering the pronunciation and articulation of certain Arabic phonemes. While previous research has focused on traditional memorization or memorization methods, there has been limited exploration into student-centered creative approaches such as singing. Many students have difficulty remembering and actively using Arabic vocabulary in everyday conversation. This can hinder their understanding of Islamic religious texts and literature, which is mostly written in Arabic. Often, the traditional memorization process is considered boring and less engaging for students resulting in their low motivation to learn. This study aims to investigate the effectiveness of innovative singing methods in overcoming phonetic challenges faced by Arabic-speaking students at the Nurul Chotib Islamic Boarding School. This study uses a qualitative descriptive method with a case study approach. The locus is the Nurul Chotib Islamic Boarding School, where data is collected through observations, interviews with teachers and students, and audio recordings of pronunciation exercises. Data analysis was carried out through data reduction, coding, and thematic interpretation to identify the impact of the singing method. The findings show that integrating melodies into Arabic pronunciation lessons significantly improves students' articulation and phonetic accuracy. Its novelty lies in the application of culturally relevant and engaging methods that increase retention and motivation. In conclusion, the main lesson that can be taken from this study is that including music in the learning process can make memorization activities more fun and effective. In addition, the contribution of this method can increase students' motivation to be more actively involved in learning, as well as strengthen their memory. Therefore, the singing method can be considered a useful alternative to improve the quality of language and religion learning in Islamic boarding schools.